Electron‐Driven Dissipation in a Tailward Flow Burst. Issue 11 (11th June 2019) - Chen, Z. Z.; Fu, H. S.; Liu, C. M.; Wang, T. Y.; Ergun, R. E.; Cozzani, G.; Huang, S. Y.; Khotyaintsev, Y. V.; Le Contel, O.; Giles, B. L.; Burch, J. L.
Abstract: Traditionally, the magnetotail flow burst outside the diffusion region is known to carry ions and electrons together (V i = V e ), with the frozen‐in condition well satisfied (E + V e × B = 0). Such picture, however, may not be true, based on our analyses of the high‐resolution MMS (Magnetospheric Multiscale mission) data. We find that inside the flow burst the electrons and ions can be decoupled (V e ≠ V i ), with the electron speed 5 times larger than the ion speed. Such super‐Alfvenic electron jet, having scale of 10 di (ion inertial length) in X GSM direction, is associated with electron demagnetization (E + V e × B ≠ 0), electron agyrotropy (crescent distribution), and O‐line magnetic topology but not associated with the flow reversal and X‐line topology; it can cause strong energy dissipation and electron heating. We quantitatively analyze the dissipation and find that it is primarily attributed to lower hybrid drift waves. These results emphasize the non‐MHD (magnetohydrodynamics) behaviors of magnetotail flow bursts and the role of lower hybrid drift waves in dissipating energies. Key Points: Electrons and ions are decoupled in magnetotail flow burst, because of the existence of a super‐Alfvenic electron jet inside the flow Such super‐Alfvenic electron jet is associated with electron demagnetization and agyrotropy and O‐line topology The super‐Alfvenic electron jet leads to strong energy dissipation and electron heating